Action Understanding in the Superior Temporal Sulcus Region - Vander Wyk, Brent C. (2009)
The posterior superior temporal sulcus (STS) region plays an important role in the perception of social acts, although its full role has not been completely clarified. This functional magnetic resonance imaging experiment examined activity in the STS region as participants viewed actions that were congruent or incongruent with intentions established by a previous emotional context. Participants viewed an actress express either a positive or a negative emotion toward one of two objects and then subsequently pick up one of them. If the object that was picked up had received positive regard, or if the object that was not picked up had received negative regard, the action was congruent; otherwise, the action was incongruent. Activity in the right posterior STS region was sensitive to the congruency between the action and the actress’s emotional expression (i.e., STS activity was greater on incongruent than on congruent trials). These findings suggest that the posterior STS represents not only biological motion, but also how another person’s motion is related to his or her intentions.